A Draft Northeast Asia Nuclear-Weapon-Free Zone Treaty: A Basis for Discussion - Umebayashi, Hiromichi (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.21 Mongolian Journal of International Affairs No.14 2007 pp.37-42